Quantitative easing and corporate innovation - Niklas Grimm; Luc Laeven; Alexander Popov (European Central Bank (ECB), 2021)
To what extent can Quantitative Easing impact productivity growth? We document a strong and heterogeneous response of corporate R&D investment to changes in debt financing conditions induced by corporate debt purchases under the ECB's Corporate Sector Purchase Program. Companies eligible for the program increase significantly their investment in R&D, relative to similar ineligible companies operating in the same country and sector. The evidence further suggests that by subsidizing the cost of debt, corporate bond purchases by the central bank stimulate innovation through a wealth transfer to innovative companies with low debt levels, rather than by supporting credit constrained firms.
Keywords: E5; G10; O3; 330; Unconventional monetary policy; quantitative easing; corporate innovation; productivity growth